2005
DOI: 10.2223/1300
|View full text |Cite
|
Sign up to set email alerts
|

Controversies about the management of invasive fungal infections in very low birth weight infants

Abstract: Como citar este artigo: Moreira ME. Controvérsias a respeito da sepse fúngica no pré-termo extremo: profilaxia e esquemas terapêuticos. J Pediatr (Rio J). 2005;81(1 Supl):S52-S58. AbstractObjective: This review encompasses the most recent publications about fungal infection in very low birthweight infants, keeping health professionals updated about this growing problem observed in neonatal units. Sources of data:Original and review articles published over the past 15 years were searched in MEDLINE and Lilacs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 38 publications
0
28
0
2
Order By: Relevance
“…Conforme os fatores de risco descritos anteriormente, esse único paciente com candidemia esteve exposto aos seguintes: peso ao nascimento menor que 1.000 g, IG menor de 30 semanas, colonização prévia por C. albicans em sítio intestinal e oral, PICC, NPT, VM, plaquetopenia, leucopenia e uso de mais de três esquemas antibióticos de amplo espectro. A terapêutica empírica foi iniciada com fluconazol baseada na piora clínica insidiosa, associada à piora dos exames laboratoriais e colonização fúngica prévia, conforme sugere a literatura 7 19,20 . A soma desses fatores pode ter retardado o início da terapêutica antifúngica e alterado o prognóstico do recém-nato.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Conforme os fatores de risco descritos anteriormente, esse único paciente com candidemia esteve exposto aos seguintes: peso ao nascimento menor que 1.000 g, IG menor de 30 semanas, colonização prévia por C. albicans em sítio intestinal e oral, PICC, NPT, VM, plaquetopenia, leucopenia e uso de mais de três esquemas antibióticos de amplo espectro. A terapêutica empírica foi iniciada com fluconazol baseada na piora clínica insidiosa, associada à piora dos exames laboratoriais e colonização fúngica prévia, conforme sugere a literatura 7 19,20 . A soma desses fatores pode ter retardado o início da terapêutica antifúngica e alterado o prognóstico do recém-nato.…”
Section: Discussionunclassified
“…Influenciam nessa prevalência, tanto a complexidade dos pacientes quanto a adoção de medidas de prevenção, controle dos fatores de risco durante o atendimento hospitalar e a experiência do serviço em questão. A instituição da profilaxia com antifúngicos nos RNs sob exposição a um grande número de fatores de risco (a exemplo do único RN que teve candidemia) deve levar em conta essas particularidades, merecendo uma discussão cuidadosa, especialmente devido ao ainda controverso embasamento bibliográfico 1,9,19,21 .…”
Section: Discussionunclassified
“…No serum concentrations or pharmacokinetic parameters of DAMB were found to be helpful in predicting the efficacy or toxicity of the drug [18]. The test dose in neonates is considered as not necessary as no adverse response to the test dose has ever been reported in infants [19,21,22,23 ].…”
Section: Deoxycholate Amphotericin Bmentioning
confidence: 99%
“…It also affects distal tubular epithelium causing renal tubular acidosis with electrolyte disturbance, notably hypokalaemia [16,51]. Nephrotoxicity is cumulative and may lead to renal failure [22]. Overall, the clinical studies including infants and children showed that amphotericin B is less nephrotoxic in infants and younger children, which may be due to its faster clearance [16].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…The present results agree with other studies that show C. parapsilosis as the most prevalent species in premature patients. This species provokes exogenous infections, since it colonizes the skin -especially the hands -of healthcare professionals, glycosylated solutions for hospital use, and central venous catheters, being associated with total parenteral nutrition (31).…”
Section: An Increase In Invasive Infections Caused Bymentioning
confidence: 99%